Trade Competitiveness in Developing Countries - Nazlı, Karamollaoğlu; Karamollaoğlu, Nazli (IGI Global, 2018)
Chapter 7

This chapter explores the various dimensions of trade competitiveness in developing countries. After discussing various definitions of competitiveness, the importance of trade competitiveness is discussed in the context of developing countries with reference to the existing literature. Subsequently, major constraints that affect trade competitiveness, particularly macroeconomic conditions, institutional and business environments, and infrastructure, are discussed. Finally, recent empirical findings on trade competitiveness are summarized.
Keywords: Developing countries; Trade competitiveness